A review on laser-induced graphene in flexible energy storage: From materials selection to biomedical applications - Lee, Soon Poh; Chee, Pei Song; Tan, Chun Hui; Chong, Kwok Feng; Lim, Eng Hock; Guan, Cao (Elsevier, 2024)
Laser-induced graphene (LIG) has emerged as a promising alternative to reduced graphene oxide (rGO), significantly impacting biomedical engineering, particularly in energy storage for medical devices. While existing reviews primarily focus on LIG properties and sensor applications, this review examines LIG’s potential as a flexible energy storage electrode for biomedical devices such as wearables and implants. This paper explores LIG from its accidental discovery to its current applications, highlighting its potential for end-user applications. It begins with a historical overview and discusses the challenges frequently faced in energy storage for biomedical applications, emphasizing the need for efficient, reliable solutions and the demand for miniaturized, flexible products. The review delves into the science of LIG, including its unique production methods and material properties, and compares it with traditional graphene, providing a competitive analysis. It then examines how LIG can be used as an electrode material in energy storage devices for wearables, implants, and drug delivery systems. Additionally, the transformative impact of LIG on drug efficacy, device performance, patient safety, and treatment outcomes are discussed. The paper also addresses the challenges of scaling up production, technical integration, and navigating the regulatory landscape. With its promising properties and performance, LIG shows potential as a key component in next-generation self-charging energy storage systems, offering transformative solutions for the healthcare sector.